Interocular amplitude differences of multifocal electroretinograms obtained under monocular and binocular stimulation conditions - Pálffy, A; Janáky, M; Fejes, I; Horváth, Gy; Benedek, Gy (Acta physiologica Hungarica, 2010)
To compare the interocular amplitude differences of the multifocal electroretinograms (mfERGs) evoked by either monocular or binocular stimulation in healthy subjects with good vision. Thirty-five subjects were included in the study. A Roland Consult RETIscan system was used. DTL electrodes were employed. First, the right and left eyes were stimulated separately, then, binocular stimulation was applied. The amplitudes of the scalar products were averaged over five concentric retinal regions (rings). The interocular amplitude differences were 21.55% (SD: ±12.72) under monocular conditions and 18.69% (SD: ±11.64) under binocular conditions. No significant differences were found between the amplitudes and variability values obtained under either monocular or binocular stimulation. Our results provided no evidence for the advantage of either binocular or monocular stimulating conditions in obtaining mfERGs. A considerable side difference was found between the mfERGs of the two eyes in almost all individual cases.